Prevalence and risk factors of Work Related Upper Limb Disorders (WRULD) Among Female Telephone Operators in a Telecommunication Centre in Kuala Lumpur - Noor Hassim Ismail,; Rafiza Shaharuddin, (Penerbit UKM, 2008)
A study was carried out on 79 female telephone operators working in a Telecommunication Centre in Kuala Lumpur to determine the prevalence of Work Related Upper Limb Disorders (WRULD) and its risk factors. Data collection for this study was done between December 2000 and May 2001. The presence of WRULD was determined based on a guided questionnaire and physical examination. The response rate for this study was 94.9% (n= 75) and results showed that the prevalence of WRULD among the female telephone operators was 48.0%: Stage 1= 38.9%, Stage 2= 19.4%, Stage 3= 38.9%, Stage 4= 0% and Stage 5= 2.8%. In the telecommunication centre, it was found that those with WRULD had a mean of 11.59±9.09 years of employment duration whereas those without WRULD had a mean of 9.89 ± 8.48 years of employment duration. None of the factors studied such as Body Mass Index, age, ethnicity, menstrual cycle, hormone replacement therapy, overtime work, duration of employment in the present unit and in the telecommunication centre differ in distribution between subjects with and without WRULD. This could be contributed by factors such as small number of subjects or the common healthy worker effect found in occupational health research. The findings studied of this study show that almost 40.0% of the workers experienced pain and neurological symptoms. Since none of the factors was found to be associated with WRULD, an elaborate study with a case-control design is needed in order to match cases and enable researchers to control the effect of confounding factors. This will ensure risk factors pertinent to WRULD in the Malaysian setting to be identified